Sharia Financing Model Based on Maq'id al-Shari‘ah for Strengthening Halal MSMEs - Jojo Jojo; Ana Frasipa; Asep Kurniawan; Devy Widya Apriadi; Mukhlis Mukhlis (STIESA Press, 2026)
Halal micro, small, and medium enterprises (MSMEs) play a strategic role in strengthening the Islamic economy and supporting national economic development. However, access to fair and sustainable Islamic financing for halal MSMEs remains limited due to constraints related to financing schemes and business capacity. This study aims to examine the current practices of Islamic financing for halal MSMEs and to formulate a maq??id al-shar?‘ah-based Islamic financing model to support sustainable business development. This research employs a descriptive qualitative approach using in-depth interviews, observation, and document analysis involving halal MSMEs and Islamic financial institutions. The findings reveal that Islamic financing for halal MSMEs is predominantly based on trade-based contracts, particularly mur?ba?ah, which tend to reflect a debt-oriented financing structure. From the perspective of maq??id al-shar?‘ah, Islamic financing has not yet fully supported the overall welfare of MSME actors, especially in terms of business mentoring and flexibility of financing schemes. This study proposes a maq??id al-shar?‘ah-based Islamic financing model that emphasizes partnership orientation, capacity building for MSME actors, and business sustainability. The proposed model is expected to serve as a reference for Islamic financial institutions and policymakers in developing more equitable, inclusive, and sustainable financing for halal MSMEs.